Impact of genome duplications in drought tolerance and distribution of the diploid-tetraploid Jasione maritima - Castro, Helena; Dias, Maria Celeste; Castro, Mariana; Loureiro, João; Castro, Sílvia (Frontiers in Plant Science, 2023)
Polyploidy has important ecological effects, including ploidy-mediated effects on morphology, breeding system and ecological tolerances. However, there is still little comprehensive research available to test its adaptive significance and its role in driving distributional patterns. This work aimed to assess the contribution of genome duplications to ecological divergence using an experimental approach with the diploid-tetraploid Jasione maritima polyploid complex. We explored if individuals with different ploidy differ in their tolerance to water deficit and if this may contribute to explaining the distribution patterns along a latitudinal gradient in the northwest Iberian Peninsula. For that, we used three cytogenetic entities: diploids and established tetraploids collected in natural populations along a latitudinal gradient, and neotetraploids synthesized from diploid populations after treatments with colchicine. Thirty plants from each of the nine populations were grown under controlled conditions with half randomly assigned to the water deficit treatment, and half used as control. We determined experimental plants' response by measuring fitness-related parameters, such as above and belowground biomass, plant water status, photosynthetic efficiency and pigments, membrane stability, antioxidant capacity and sugars content. Our data shows that biomass, chlorophyll content, photochemical quenching (qP) and non-photochemical quenching (NPQ) in neotetraploids and established tetraploids were significantly higher than in diploids and that these differences could be attributed to genome duplications. In response to the water deficit, diploids seem to use a strategy of avoidance, whereas tetraploids seem to employ the strategy of tolerance to overcome water deficit stress, which appears equally efficient. Additionally, we did not observe a response pattern along the latitudinal gradient of the distributional range of the J. maritima complex. The results indicate that the response to water deficit is population dependent. Further studies are necessary to understand the role of ploidy in explaining the distribution patterns of the J. maritima complex.